Therapeutic Outcomes in AIDS-Associated Kaposi’s Sarcoma Patients on Antiretroviral Therapy Treated with Chemotherapy at Two Tertiary Hospitals in Lusaka, Zambia - Mtonga, Watson (Curr HIV Res, 2018)
The incidence of HIV-associated Kaposi’s sarcoma (KS) remains high in Zambia in the antiretroviral therapy era. The most efficacious treatment regimen for KS has yet to be established. In both developed and developing countries, treatment regimens have had limited efficacy. Late presentation in Africa affects therapeutic outcomes. OBJECTIVE: The aim of this study was to determine therapeutic outcomes of epidemic KS patients on combination antiretroviral therapy (cART) after completion of six cycles of Adriamycin, Bleomycin, and Vincristine (ABV) chemotherapy. METHODS: This was a descriptive cross-sectional study. Study participants were drawn from a study database of confirmed incident KS patients seen at the Skin Clinic of the University Teaching Hospitals (UTH) during the period between August, 2015 and September, 2016. RESULTS: Of the 38 successfully recruited study participants, a complete response was documented in 18 (47%) after 6 cycles of ABV whereas 20 (53%) experienced a partial response. KS recurrence was observed in 8 (44%) of the individuals that experienced an initial complete response. At the time of the study, clinical assessment revealed that KS lesions had completely regressed in 21 (55%) of all the patients. CONCLUSION: ABV chemotherapy appears ineffective in long-term resolution of epidemic KS patients on ART. Recurrence rates are high after chemotherapy in patients that experience initially favorable responses to treatment. There is a need to diagnose KS earlier, and to develop more efficacious treatment options in order to reduce recurrence rates for epidemic KS.